An Exploration of Gendered Food Bias in Central Rural North Indian Homes - Chandra, Nishita (Auckland University of Technology, 2020)
The North Indian society is deeply patriarchal and as a result, the women often suffer. The cultural and societal expectations of women burden their health and well-being throughout their lives, affecting various parts of their lives including their relationship with food. Previous studies have focused on and identified the nutritional discrepancies between men and women and the nutritional effects of a food bias, but have not ventured into a socio-cultural aspects that further the nutritional bias. This study aims to explore the underlying reasons and mechanisms behind a gendered food bias within rural North Indian society. Secondary data were collected through Indian YouTube channels portraying the real lives of the people in rural North India between 2015 and 2019. According to the findings, family hierarchy, roles of service for women, and traditional norms of behaviour were overarching themes that promote a gendered food bias in rural North Indian society. The supporting mechanisms are how food is prepared, served and consumed, as within the rural food cycle, these activities show a visible bias in favour of men. This study provided insights and practical and theoretical implications such as explaining the mechanisms that preserve the food bias against women in North Indian society, and recommends initiatives from government bodies in these areas that would help educate people to make them aware of the existent bias and how it affects women and girls.
Keywords: Gender; Food bias; North India; Female bias